In Vitro Chloroquine Resistance in Plasmodium falciparum Isolates from Tertiary Care Hospital. (24th September 2012) - Shujatullah, Fatima; Khan, Haris M.; Khatoon, Abida; Khan, Parvez A.; Ashfaq, Mohammad
Abstract : Chloroquine (CQ) has been the mainstay of treatment of malaria for decades. This cost-effective and safe drug has become ineffective for treatment of falciparum malaria in many parts of the world due to development of resistance by the parasite. In addition CQ is not gametocytocidal for P. falciparum and thus cannot block transmission. The extent of problem of chloroquine resistance in P. falciparum is increasing every year. The study was done in period of 2 years. A total of 5653 specimens were examined for malarial infection by employing different diagnostic modalities. Four hundred and thirty-five were found to be positive for P. falciparum by using different diagnostic techniques. All positive specimens were cultured on RPMI 1640 medium; only 108 were found to be culture positive. Sensitivity of isolates to chloroquine was done using Mark III WHO sensitivity plates. The prevalence of malaria infection was found 9.54% in 2010. There were schizont formation at 8 pmol/liter or more of chloroquine concentration in 26 isolates. The emergence of chloroquine (CQ) resistance pattern in Aligarh isolates increases. Antimalarial agents should be used with caution; monotherapies should be avoided.